Bridging Heterodox Views on Language and Symbols: Gilbert Durand’s Imaginaire and Mark Johnson’s Image Schemata - García-Valero Benito (Gestalt Theory, 2019)
This paper aims to bridge anthropological and cognitivist research undertaken by Gilbert Durand and Mark Johnson, who studied the phenomenon of meaning making in a similar way, although they had to use different terminology as their disciplines demanded. Durand established systematization for analyzing symbolism by taking into account the position of the body and the perceptions determining the underlying schemata of symbols. Two decades later, Mark Johnson described image schemata as gestalts having an internal structure derived from bodily perceptions. Owing to these similarities, a comparison between Durand and Johnson’s theories is offered first. In the second place, I reviewed the cognitive value of the anthropological regimes of imaginaire described by Durand. During the analysis, the terminology used by these theorists (like ‘image schemata’ or ‘axiomatic schemata’) was comparatively analyzed to find common ground between their positions. In conclusion, the need for recovering theories of imagination proposed by heterodox scholars like Durand is highlighted, since they anticipate the role of images and imagination not only in language, as Johnson demonstrated, but also in the formation of anthropologically relevant symbols, which are of interest for the analysis of literature and other arts.